Effect of amino acid deficiency on precaecal amino acid digestibility in broiler chickens. Issue 3 (31st January 2019) - Siegert, Wolfgang; Ganzer, Christian; Kluth, Holger; Rodehutscord, Markus
Abstract: In this study, we determined whether deficient dietary amino acid (AA) concentrations influence the precaecal (pc) AA digestibility when determined using the regression approach. We mixed two basal diets. Basal diet 1 was deficient in essential AAs, whereas adequate AA concentrations were ensured in basal diet 2 by adding free AAs. Rapeseed cake and full‐fat soya beans as test ingredients were included in the basal diets at levels of 100 and 200, and 150 and 300 g/kg, respectively, at the expense of maize starch. Each diet was tested with six replicates of 10 broiler chickens each. The feed intake of the chickens that were fed diets based on basal diet 2 was similar, whereas the feed intake of the chickens that were fed diets based on basal diet 1 differed considerably. The numerical differences in pc AA digestibility determined with basal diet 1 or 2 ranged from 2.6 percentage points to 20.8 percentage points in rapeseed cake and from 0.5 percentage points to 15.2 percentage points in soya beans. Across all measured AAs, the average differences were 10.1 percentage points and 5.4 percentage points in rapeseed cake and soya beans, respectively. The differences in the estimated pc AA digestibility between the basal diets were probably caused by different basal endogenous AA losses in the digesta between treatments as a consequence of different feed intake. Adequate AA concentrations and test ingredient levels that are specifically adjusted to avoid a negative effect on feed intake are recommended for future studies.